Growth data and tumour risk of 32 Chinese children and adolescents with 45,X/46,XY mosaicism - Lili Pan; Zhe Su; Jianming Song; Wanhua Xu; Xia Liu; Longjiang Zhang; Shoulin Li; on behalf of the multidisciplinary collaboration team of DSD management at Shenzhen Children's Hospital (BMC, 2019)
Abstract Background The aim of this study was to review the growth data, gonadal function and tumour risk of children and adolescents with 45,X/46,XY mosaicism who presented to a single centre in China. Methods We conducted a retrospective review of the records of 32 patients with 45,X/46,XY mosaicism or variants who were hospitalized from August 2005 to September 2018. The main outcomes measured were growth data, genital phenotype, gonadal function, gonadal position, and histological results. Results A total of 32 patients were included. The age at diagnosis ranged from 0.6 to 16.3 years. Nineteen patients exhibited ambiguous genitalia, 12 had short stature, and 1 showed a lack of breast development. Seventeen patients were raised as males, and 15 were raised as females. The external masculinisation score (EMS) of patients raised as male was 4.5 (1~12) [median (range)]. The EMS of the females was 0 (0~1.5) [median (range)]. Patients showed normal heights under 2 years old, with a height SDS of 0 (− 1.5~1.4) [median (range)]. Growth appeared to decelerate after age 2 years, with SDS decreased to − 2.8 (− 3.0~ − 0.9) [median (range)]. The percentage of short stature was higher in females than in males (76.9% vs 50.0%). Twenty-five patients had gonadal pathological results. Complete gonadal dysgenesis (CGD) and mixed gonadal dysgenesis (MGD) were the most common pathogenic subtypes, accounting for 48.0 and 36.0%, respectively. Ovotesticular tissue was observed in only 4.0% of patients. Gonadoblastoma and positive OCT3/4 results were found in 18.8% of gonads in children over 2 years of age. Palpable gonads accounted for 50% of these. All patients who had gonadoblastoma were raised as females. Conclusions Patients with 45,X/46,XY might have normal heights until 2 years old. Growth decelerations after 2 years of age were common. Patients who are being raised as females seemed to be shorter than males. CGD and MGD were the most common gonadal pathogenic subtypes. The tumour risk is high in these patients, even in palpable gonads and female patients.